2007
DOI: 10.1158/0008-5472.can-07-0120
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone-Induced Apoptosis in Human Prostate Cancer Cells Is Caused by Reactive Oxygen Intermediate–Dependent Activation of c-Jun NH2-Terminal Kinase

Abstract: Guggulsterone, a constituent of Indian Ayurvedic medicinal plant Commiphora mukul, causes apoptosis in cancer cells but the sequence of events leading to cell death is poorly understood. We now show that guggulsterone-induced cell death in human prostate cancer cells is caused by reactive oxygen intermediate (ROI)-dependent activation of c-Jun NH 2 -terminal kinase (JNK). Exposure of PC-3 and LNCaP cells to apoptosis inducing concentrations of guggulsterone resulted in activation of JNK and p38 mitogen-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 48 publications
(61 reference statements)
4
77
1
2
Order By: Relevance
“…In addition, typical DNA fragmentation, a hallmark of apoptosis, was also observed subsequent to the cells being treated with 60 µmol/l Z-guggulsterone for 48 and 72 h. Flow cytometry revealed that Z-guggulsterone induced apoptosis in cholangiocarcinoma Sk-ChA-1 and Mz-ChA-1 cells in a time-and dose-dependent manner. Consistently, the present findings were supported by previous studies that identified similar effects of guggulsterone in other types of cancer cells (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, typical DNA fragmentation, a hallmark of apoptosis, was also observed subsequent to the cells being treated with 60 µmol/l Z-guggulsterone for 48 and 72 h. Flow cytometry revealed that Z-guggulsterone induced apoptosis in cholangiocarcinoma Sk-ChA-1 and Mz-ChA-1 cells in a time-and dose-dependent manner. Consistently, the present findings were supported by previous studies that identified similar effects of guggulsterone in other types of cancer cells (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 93%
“…As the main substrate of caspases, the alteration in the expression of cleaved PARP also supports this conclusion. Consistent with the present results, several other studies have reported that caspase-dependent apoptosis induced by guggulsterone also occurred in prostate and colon cancer cells (13,16). Additional studies investigating the possibility that guggulsterone triggers apoptosis through caspase-independent pathways are required in the future, as the caspase inhibitors used in the present study did not completely abolish guggulsterone-induced apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous works [41][42][43] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Mencarelli et al, 19…”
Section: Discussionunclassified
“…This is typical for prostate cells [17][18][19][20][21][22][23][24][25], pancreatic cancer cells [26][27][28][29][30][31][32][33], melanoma cells [34][35], breast cancer cells [36][37][38][39], and other cancer cells [40][41][42][43][44][45][46][47][48][49][50]. It is important that the elevated ROS formation in cancer cells can have both surviving and hindering effects.…”
Section: Cancermentioning
confidence: 99%